A Non-coding HES1 Variant Predisposes Children to Congenital Heart Disease in Chinese Population - Song, Yangliu; Chen, Weicheng; Huang, Zitong; Tian, Guixiang; Li, Mengru; Zhao, Zhengshan; Feng, Zhiyu; Wu, Feizhen; Qian, Maoxiang; Ma, Xiaojing; Sheng, Wei; Huang, Guoying (Frontiers in Cell and Developmental Biology, 2021)
Background: As a key component in the NOTCH signaling pathway, HES1 plays an important role in vertebrate heart development. Variants in the HES1 coding sequence are known to be associated with congenital heart disease (CHD). However, little is known about HES1 non-coding sequence variants and their association with the risk of developing CHD. Method and Results: We initially analyzed the non-coding sequence of the HES1 gene in 12 unrelated CHD families by direct sequencing and identified a previously unreported promoter region variant (NM_005524.4: c.−1279−1278 insAC, rs148941464) in the HES1 gene in four CHD families. The homozygous variant in patients was inherited from carrier parents with normal phenotypes, indicating a likely recessive genetic model. Given that the HES1 gene is predicted to be likely to exhibit haploinsufficiency (%HI: 11.44), we hypothesized that the HES1 homozygous variant is a genetic risk factor underlying CHD. We then carried out sequencing of this HES1 variant in 629 sporadic non-syndromic CHD cases and 696 healthy controls and performed association analysis. Interestingly, we observed a significant association of the homozygous HES1 promoter variant with CHD (18.92% of cases vs. 9.91% of controls; OR: 2.291, 95% CI: 1.637-3.207, p = 9.72 × 10−7). No significant association with CHD was observed for the HES1 promoter heterozygous variant (p > 0.05). However, association analysis tests of the HES1 homozygous variant with each subtype of CHD revealed that this homozygous variant was strongly associated with transposition of the great arteries (TGA) (OR: 3.726, 95% CI: 1.745-7.956, p = 0.0003). Moreover, the prevalence of HES1 homozygous variants in CHD patients with TGA (27.66%) was significantly higher than that in patients with other CHD subtypes or controls. Similar results were observed in a replication group of TGA (n = 64). Functional studies demonstrated that the homozygous variant in the HES1 promoter can disrupt its ability to bind RXRA, an inhibitory transcription factor, which results in abnormally high expression of the HES1 gene, indicating that this variant harbors gain-of-function effects. Conclusions: Our findings reveal that the non-coding homozygous variant in the HES1 promoter has a gain-of-function effect and is associated with an increased risk of CHD development, especially the severe TGA subtype.